The dual nature of adaptive coordination in teams: Balancing demands for flexibility and stability. (May 2018) - Grote, Gudela; Kolbe, Michaela; Waller, Mary J.
Adaptive team coordination is a central topic in the team dynamics literature. Most team adaptation research to date addresses team responses to demands for flexibility triggered by dynamic external forces. Little explicit attention has been paid to demands for stability created by continued pressures on efficiency and control. To capture this dual nature of adaptive coordination, we propose to characterize adaptation triggers in terms of stability and flexibility demands and suggest four modes of adaptive coordination that enable teams to adequately balance these demands. Grounded in team as well as organizational literatures, we explicate the specific patterns of coordination mechanisms comprising each mode of coordination, termed experiential, exploitative, exploratory, and ambidextrous coordination. The new insights offered into team adaptive coordination can spur research that further integrates team and organizational perspectives on adaptation processes.